Experimental Investigation of Cocoa Pod Biomass Carbonization: A Pathway to Sustainable Energy - Christelle Adjo OGO; Bernabé Marί Soucase; Amal Bouich (Sustainable Chemical Engineering, 2025)
This study evaluates the valorization potential of cocoa pods, mainly sourced from the Sud-Comoé region of Côte d'Ivoire, through controlled thermal pyrolysis to produce biochar. Two experiments were conducted at final temperatures of 331.29 °C and 357.92 °C, yielding biochars with distinct characteristics. The first trial, with a 55% mass yield, produced a biochar with a Lower Heating Value (LHV) of 14.097 MJ/kg, making it suitable for agronomic applications. The second trial, although yielding only 35%, resulted in a higher-energy biochar with an LHV of 22.158 MJ/kg, positioning it closer to high-performance biomasses such as coconut husks (28-32 MJ/kg) and sawdust (18-22 MJ/kg). Processing one ton of cocoa pods is estimated to yield between 350 and 550 kg of biochar, potentially sequestering between 770 kg and 963 kg of CO2. Compared to direct combustion, this approach avoids approximately 1,063 kg of CO2 emissions per ton of biomass processed. Thermodynamic modeling using the Hirn cycle estimated the energy potential between 3.662 and 5.815 kWh per ton, depending on yield and LHV. These findings highlight the effectiveness of moderate-temperature pyrolysis in producing energy-rich biochar and reinforce the potential for sustainable valorization of cocoa pod residues within Côte d'Ivoire's agro-environmental development framework.